Identification of Parabodo caudatus (class Kinetoplastea) in urine voided from a dog with hematuria. (January 2015) - Vandersea, Mark W.; Birkenheuer, Adam J.; Litaker, R. Wayne; Vaden, Shelly L.; Renschler, Janelle S.; Gookin, Jody L.
A voided urine sample, obtained from a 13-year-old intact male dog residing in a laboratory animal research facility, was observed to contain biflagellate protozoa 5 days following an episode of gross hematuria. The protozoa were identified as belonging to the class Kinetoplastea on the basis of light microscopic observation of Wright–Giemsa-stained urine sediment in which the kinetoplast was observed basal to 2 anterior flagella. A polymerase chain reaction (PCR) assay using primers corresponding with conserved regions within the 18S ribosomal RNA gene of representative kinetoplastid species identified nucleotide sequences with 100% identity to Parabodo caudatus. Parabodo caudatus organisms were unable to be demonstrated cytologically or by means of PCR in samples collected from the dog's environment. The dog had a history of 50 complete urinalyses performed over the 12-year period preceding detection of P. caudatus, and none of these were noted to contain protozoa. Moreover, the gross hematuria that was documented 5 days prior to detection of P. caudatus had never before been observed in this dog. Over the ensuing 2.5 years of the dog's life, 16 additional complete urinalyses were performed, none of which revealed the presence of protozoa. Bodonids are commonly found in soil as well as in freshwater and marine environments. However, P. caudatus, in particular, has a 150-year-long, interesting, and largely unresolved history in people as either an inhabitant or contaminant of urine. This historical conundrum is revisited in the current description of P. caudatus as recovered from the urine of a dog.